The relationship between effective communication and customers' satisfaction: a study in four and five star hotels in Kuching - Aniza Baizura, Ariffin (Universiti Malaysia Sarawak (UNIMAS), 2012)
Qnhospitality industry, revenues are driven by guest satisfaction. Therefore, in order to satisfy the customers, the service providers must ensure that the needs and wants of the customers are met. Many researchers agreed that effective communication skills greatly influence customers' satisfaction. The purpose of this paper is to examine the relationship between effective communication and customers' satisfaction in four and five star hotels in Kuchin~125 respondents have been chosen randomly as a sample. The chosen respondents consist of 47 male and 78 female. Respondents are strictly those who have ever stayed in the four and five star hotels in Kuching city. The instrument of this study was a set of questionnaire which consist 3 parts; respondents' background, effective communication and customer satisfaction. Data we collected and then were analyzed by using SPSS version 17.0. Results were analyzed with factor analysis, Pearson correlation analysis and multiple regression analysis. Factor analysis has extracted three factor solutions to be the most interpretable results; basic communication skills, communication clarity and information accessibility. It was found that all these three effective communication dimensions have a positive relationship with customers' satisfaction, with a beta of 0.32, 0.22 and 0.19 respectively. Overall, the finding of this study is consistent with the previous literatures (Bitner et ai., 1994; Heskett et ai., 1997; Hokanson, 1995; Webster, 1991 and Kahle, 2002), that there is a positive relationship between effective communication and customer satisfaction.